Modeling of suspension polymerization of vinyl chloride with a simplified population balance equation - Bárkányi, Ágnes; Németh, Sándor; Lakatos, G. Béla (Acta Agraria Kaposváriensis, 2010)
Suspension polymerization of vinyl chloride is investigated using a simplified population balance equation, in which aggregation of primary particle is negligible. Polymerization proceeds in two phase: the first one is the monomer-rich phase and the other one is the polymer-rich phase. A mathematical model that provides a suitable method for determining the primary particle size distribution in the reactor is developed. The morphological and mechanical properties of the polymer grades are highly influenced by the primary particle size distribution. So, if we can determine this property appropriately, we will take a very important step toward of appropriate production of tailor made grades. The primary particle size distribution is determined by the nucleation and growth of primary particles. These processes are largely influenced by agitation, the reactor temperature, electrolyte as well as the concentrations of applied stabilizers.